2011
DOI: 10.1002/j.2161-0045.2011.tb00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Career and Life Stress, Negative Career Thoughts, and Career Decision State: A Cognitive Information Processing Perspective

Abstract: According to cognitive information processing theory, career thoughts mediate the relationship between career and life stress and the ensuing career decision state. Using a sample of 232 college students and structural equation modeling, this study found that an increase in career and life stress was associated with an increase in negative career thinking and that an increase in such thoughts was associated with a lower level of decidedness and satisfaction with career choice. However, when the variation assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 19 publications
(21 reference statements)
6
73
0
7
Order By: Relevance
“…Students' career pathways have gained momentum since subject and career guidance have been introduced at school level together with 'open days' hosted at most of the South African 210 academic institutions assisting scholars in guiding students in their degree choices and futures careers. Some students' profiles can often lead to students who become completely indecisive in choosing subjects for a degree, choosing a career and/or experiencing uncertainty among career choices that guarantee employability (Bullock-Yowell, Peterson, Reardon, Leierer and Reed 2011;Weatherby, Winne, MacAllister and Nesbit 2008;Eddy, Burke and Fiksenbaum 2008). While some students' profiles indicate that students who prefer to study towards becoming Chartered Accountants (CAs) indicate lower levels of subject indecision since the professional body together with academic institutions provide a fixed curriculum for the degree (SAICA 2016;Jordaan, Burger and Smithard 2009;Papageorgiou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Students' career pathways have gained momentum since subject and career guidance have been introduced at school level together with 'open days' hosted at most of the South African 210 academic institutions assisting scholars in guiding students in their degree choices and futures careers. Some students' profiles can often lead to students who become completely indecisive in choosing subjects for a degree, choosing a career and/or experiencing uncertainty among career choices that guarantee employability (Bullock-Yowell, Peterson, Reardon, Leierer and Reed 2011;Weatherby, Winne, MacAllister and Nesbit 2008;Eddy, Burke and Fiksenbaum 2008). While some students' profiles indicate that students who prefer to study towards becoming Chartered Accountants (CAs) indicate lower levels of subject indecision since the professional body together with academic institutions provide a fixed curriculum for the degree (SAICA 2016;Jordaan, Burger and Smithard 2009;Papageorgiou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When individuals are compelled to make career decisions in stressful times, several salient factors emerge that may bear on their motivation to engage in career exploration, namely (a) the degree of indecision or uncertainty with respect to a career choice, and (b) the extent of dissatisfaction with the choice. These two items were collectively referred to as the career decision state (CDS; Bullock-Yowell et al, 2011). In this study, another variable was added to the concept of CDS, specifically, the amount of tension or stress to make a decision connoting the extent of urgency or time pressure on individuals to make a decision.…”
Section: Prior Researchmentioning
confidence: 99%
“…Results of the analyses suggested that goal instability may serve as an initial global screening measure of readiness for career exploration in a classroom environment. All three elements of the CDS were associated with negative career thoughts (Bullock-Yowell et al, 2011). Bullock-Yowell, Reed, Mohn, Galles, Peterson, and Reardon (2015) used Structural Equation…”
Section: Prior Researchmentioning
confidence: 99%
See 2 more Smart Citations